성과관리 제도운영 효과성 영향요인 연구: 경찰조직에서 투명성을 중심으로 - 강영철; Kang Young C; 최낙범; Choi Nakbum (한국거버넌스학회보, 2016)
성과관리 제도는 개인과 조직의 성과를 정의하고 업무목표를 규정하며, 성과측정과 체계적인 관리를 통해 지속적으로 조직성과를 향상 시키는 것을 목적으로 한다. 따라서 성과관리 제도의 성공적인 운영은 조직전반의 관리, 운영 및 실제 업무와 관련된 여러 가지 요인들에 영향을 받는다. 그간 선행연구에서는 기관장의 관심, 결과의 활용가능성, 성과지표에 대한 신뢰, 업무 연관성, 제도이해와 같은 요인들이 기대효과에 영향을 미치는 것으로 제시되어왔다. 하지만 명확한 성과기준이 존재하지 않는 공공부문에서 어떤 요인들이 중요하게 고려되어야 하는지에 대한 경험적 연구는 여전히 부족하다. 본 연구에서는 경찰조직의 맥락에서 성과관리 제도운영의 효과성에 영향을 미치는 요인들을 투명성을 중심으로 살펴보았다. 경찰업무는 일반 행정기능에 비해 더 복잡한 측면이 존재하며 명확한 성과기준이 존재하지 않는다. 특히 엄격한 명령체계에 따른 위계적인 조직문화 내에서 성과평가와 제도 운영이 투명하게 이루어지고 있다고 판단하는 것은 제도효과성 인식에 있어서 매우 중요하게 작용할 수 있다. 경찰관 10,619명을 대상으로 한 설문조사를 통해 성과관리 제도 기대효과에 미치는 영향요인을 투명성의 조절효과를 중심으로 살펴본 결과, 투명성, 결과활용, 지표신뢰, 제도이해, 업무연관성, 평가자 신뢰는 기대효과에 유의미한 영향을 미치는 것으로 나타났다. 또한 투명성은 결과활용, 제도이해, 업무연관성이 기대효과에 미치는 영향을 강화하는 것으로 나타났다. 즉, 경찰조직에서 성과관리 제도는 실질적인 운영과정에서의 투명성과 구성원 간의 신뢰확보, 의사소통 측면을 가장 중요하게 고려해야할 필요성이 있다는 점을 시사한다고 볼 수 있다. Performance management system(PMS) aims to enhance organizational performance through systematic measurement and sustainable management of performance and goals. Therefore, the success of PMS is determined by many factors relating overall operations and tasks of the organization. Previous studies have revealed that employee`s perception on operations and processes of the system can influence on effectiveness of it. However, empirical research on public organizations is still limited. Therefore, further research is needed to retest results of former studies and explore new influencing factors. This study attempts to examine influencing factors on employees` perception on expected effectiveness of PMS in police organization focusing on transparency. Measuring police performance is more complicated and difficult than that of other pubic organizations. Therefore, understanding multifaceted features of the police activities is crucial for the success of PMS. Especially, operating the system with transparency can be very influential in an organization like police which has rigidly hierarchical culture. In this study, we examined key factors influencing an individual`s attitude to the PMS using a survey data which was collected from 10,619 police officers. We also tested moderating effects of the perception of transparency. Results show that transparency, applicability, trust on indicators, understanding the system, job relevance, and trust on evaluators have positive and significant impacts on the dependent variable. Results also show that transparency have positive moderating effects on relationships between independent variables- applicability, understanding, job relevance- and the dependent variable. Based on the results, this article concludes with a discussion of the implications for our understanding of PMS in the police organization.